2014
DOI: 10.1186/1471-2253-14-35
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fluid intervention on complications and length of hospital stay after pancreaticoduodenectomy (Whipple’s procedure)

Abstract: BackgroundThere is limited information on the impact on perioperative fluid intervention on complications and length of hospital stay following pancreaticoduodenectomy. Therefore, we conducted a detailed analysis of fluid intervention in patients undergoing pancreaticoduodenectomy at a university teaching hospital to test the hypothesis that a restrictive intravenous fluid regime and/or a neutral or negative cumulative fluid balance, would impact on perioperative complications and length of hospital stay.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
53
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 19 publications
7
53
1
2
Order By: Relevance
“…According to Brandstrup et al, 24 there was significantly fewer complications in the patients received restrictive fluids in comparison with the group with the standard regime of intravenous fluids. Similar results were reported in the studies conducted by Abraham-Nordling et al, 21 de Aguilar-Nascimento et al, 25 Kocian et al, 26 and Weinberg et al 27 However, Warrillow et al 28 stated that pre-operative fluid therapy is associated with more complications (about 57%) in major surgeries of digestive system. Of course, it should be noted that accompanying background diseases, as well as type and location of surgery, may be involved in emerging of complications independent from fluid therapy.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…According to Brandstrup et al, 24 there was significantly fewer complications in the patients received restrictive fluids in comparison with the group with the standard regime of intravenous fluids. Similar results were reported in the studies conducted by Abraham-Nordling et al, 21 de Aguilar-Nascimento et al, 25 Kocian et al, 26 and Weinberg et al 27 However, Warrillow et al 28 stated that pre-operative fluid therapy is associated with more complications (about 57%) in major surgeries of digestive system. Of course, it should be noted that accompanying background diseases, as well as type and location of surgery, may be involved in emerging of complications independent from fluid therapy.…”
Section: Introductionsupporting
confidence: 74%
“…Similar to this study, de Aguilar-Nascimento et al 25 suggested that restrictive fluid therapy protocol leads to shorter hospitalization period. According to Weinberg et al, 27 restrictive fluid therapy is associated with shorter hospitalization period. Contrary to the above-mentioned findings, Abraham-Nordling et al 21 stated that restrictive pre-operative fluid therapy does not affect shorter hospitalization period.…”
Section: Introductionmentioning
confidence: 99%
“…Профилактику развития панкреатической фистулы подкожным введением раствора октреотида (200 мкг за 1 ч до операции и в послеоперационном периоде в дозе 100 мкг 3 раза в день в течение 5-7 дней) использовали только в случае высокого риска несостоятельности панкреатоэнтероанастомоза -при неизмененной, мягкой или хрупкой ПЖ с узким (до 3 мм) протоком. Важным мы считали ограничение введения жидкости: во время и после операции водный баланс должен быть около нуля, не превышая его более чем на 500 мл [25,61]. Этап 1.…”
Section: материал и методыunclassified
“…Nevertheless, maintaining adequate intravascular fluid is crucial for normal organ perfusion. Inappropriate intravascular fluid intervention is strongly associated with postoperative complications after major abdominal surgery [24][25][26][27][28][29][30] . However, the safety of fluid in the perioperative period of abdominal surgery remains unclear [31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%